2020
DOI: 10.21608/ejabf.2020.104648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals in irrigation water of different fish farms on the quality of cultured fish

Abstract: Results indicated that most of the highest averages of all heavy metal concentrations in water, sediment and fish muscular tissues were recorded from Bahr El-Baqar fish farm and their lowest values from El-Abbasa fish farm. The highest contamination factors for most heavy metals were recorded in Bahr El-Baqar fish farm and the lowest in El-Abbasa fish farm. The present study concluded that El-Abbassa fish farm has low pollution and the other fish farms (Edko, Mariout, and Bahr El-Baqar) have progressive deteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A study by Santhakumaran et al (2020), showed that algae are a valuable mineral source and some species contain Fe ranging from 0.08 to 10.21 mg/g while Zn content can range from 0.01 to 1.10 mg/g. The bioavailability of minerals from ingested food can be influenced by the ingestion rate, the nature of the food, and the effectiveness of food assimilation (El-Khatib et al, 2020;Marengo et al, 2018). The microminerals concentration in the maturation pond and the MBR were listed in the order Fe > Zn > Mn.…”
Section: Mbrmentioning
confidence: 99%
“…A study by Santhakumaran et al (2020), showed that algae are a valuable mineral source and some species contain Fe ranging from 0.08 to 10.21 mg/g while Zn content can range from 0.01 to 1.10 mg/g. The bioavailability of minerals from ingested food can be influenced by the ingestion rate, the nature of the food, and the effectiveness of food assimilation (El-Khatib et al, 2020;Marengo et al, 2018). The microminerals concentration in the maturation pond and the MBR were listed in the order Fe > Zn > Mn.…”
Section: Mbrmentioning
confidence: 99%
“…(Silim 2015). The fact that domestic, municipal, agricultural, and industrial wastes are continuously discharged into the lake makes El-Max pumping site essential to maintain the lake water level about 2.8-3.0 m below the mean sea level (Khalil et al 2013;El-Khatib et al 2020).…”
Section: Mariout Lake Inflows and Outflowsmentioning
confidence: 99%
“…It is a number that describes the bioaccumulation as a ratio of the concentration of a chemical inside an organism to its concentration in the surrounding environment (Goher et al 2015). The bioaccumulation factor (BAF) of a heavy metal in fish tissues was determined using the equation according to El-Khatib et al (2020).…”
Section: Bioaccumulation Factor (Baf) Estimationmentioning
confidence: 99%
See 2 more Smart Citations